(untitled) (Memorias Sifored - Encuentros Educación UAN, 2021)
This presentation shows the interest of a group of researchers to check, analyze and propose a route to widen the B-learning strategy in courses that, due to their characteristics, tend to improve the reading and writing competence of the students of the Bachelor’s degrees who belong to the School of Educational Sciences. The academic benefits of the implementation of B-learning is the use of ICT in dynamic and interactive educational environments that promote autonomous, self-regulated and collaborative learning, with virtual or face-to-face meetings. At UNAD, the adoption of b-learning strategy is institutionalized with the 2015 Development Plan onwards, to motivate first-enrolment students, in order to influence retention and permanence levels in the educational system. The strategy is oriented in a determined number of mandatory, elective or highly complex courses. The research focuses on five courses, whose formative aims point to reading and writing processes; two of these courses are mandatory for all students in the professional and technical programs, another one fulfills the dual function of being mandatory for one program and elective for others, and two additional courses that are part of the Virtual Center for Writing, Language and Expression , which do not have the mentioned strategy; this study aims to show the need to widen the strategy to more courses that contribute to the students’ formation.